Employment, innovation and productivity: Evidence from Italian microdata - Bronwyn Hall; Francesca Lotti; Jacques Mairesse (Institute for Fiscal Studies (IFS), 2006)
Italian manufacturing rms have been losing ground with respect to many of their European competitors. This paper presents some empirical evidence on the e®ects of innovation on employment growth and therefore on rms' productivity with the goal of understanding the roots of such poor performance. We use rm level data from the last three surveys on Italian manufacturing rms conducted by Mediocredito-Capitalia, which cover the period 1995-2003. Using a modied version of the model proposed by Harrison, Jaumandreu, Mairesse and Peters (2005), which separates employment growth rates into those associated with old and new products, we provide robust evidence that there is no employment displacement e®ect stemming from process innovation. The sources of employment growth during the period are split equally between the net contribution of product innovation and the net contribution from sales growth of old products. However, the contribution of product innovation is somewhat lower than that for the four comparison European countries considered by Harrison et al. – Innovation ; employment ; productivity ; Italy
Keywords: L60; O31; O33; 330; Verarbeitendes Gewerbe; Innovation; Industrielle Beschäftigung; Produktivität; Italien